Factors associated with the presentation of tenosynovitis in broiler chicken - Duarte Rodríguez, Luz Zoraya; Tarazona Daza, Ilein Karine (Spei Domus, 2022)
Poultry production in Colombia is one of the main activities given the high consumption of this protein at the national level, due to its easy access for the entire population, according to the indicators of the Ministry of Agriculture, the poultry sector registered in the 2020 a growth of 4.5% and according to FENAVI for 2020 the per capita consumption of chicken was 35.5 kg / year. The industry has always been affected by the different diseases that affect birds, one of these is viral arthritis or tenosynovitis which is a serious economic and health problem for the industry.The objective of this research was to carry out a literature review of the current state of knowledge about the factors associated with the presentation of tenosynovitis in broilers. For this, a review was carried out in databases (ScienceDirect, Pubmed, Scopus, among others) to search for documents and articles related to the subject. A total of 359 articles were found, of which 12 were finally selected for the review. Given that viral arthritis or tenosynovitis is a disease caused by avian arboviruses (ARVs), the findings of the different studies associated with ARVs show that in recent years these pathogens have evolved through greater genetic diversity and their pathogenicity. Therefore, since the control of the disease associated with ARV infection is increasingly difficult, new prevention and control measures are required, since vaccination has proven not to be totally effective.
Keywords: infectious disease; PCR; avian reovirus; viral arthritis